(untitled) (Nonconventional Technologies Review, 2024)
A new and original dosing of alumina-silicate wastes in preparing mixture of the geopolymeric material is presented in this paper. Unlike the usual preponderant utilization of fly ash and ground blast furnace slag, the article adopted a major proportion of concrete waste from building demolition compared to the other two mentioned components, aiming at obtaining high strength geopolymers. The result of applying this new dosing in the material mixture activated with alkaline solution was increasing the compression and flexural resistance of the geopolymer, especially at earl age of curing (7 days). The experiment showed that by mixing 310-470 kg·m-3 of concrete waste from demolition, 230-254 kg·m-3 of fly ash, 102-120 kg·m-3 of blast furnace slag, and 4 kg·m-3 of silica fume, the best performing mechanical characteristics of the geopolymer can be obtained. The optimal values ​​of denseness were between 1.64-2.04 g·cm-3 and those of heat conductance were between 0.218-0.306 W·m-1·K-1.